Comparison of positivity frequency of bcl-2 expression in prostate adenocarcinoma with low and high Gleason score - Hering, Flávio Luiz Ortiz (2001)
CONTEXT: Multiple genetic and epigenetic factors have been implicated in the oncogenesis and progression of prostate cancer. The major difficulty is in that the clinical management stems from the reality that reliable and accurate prognostic biomarkers are not available and that effective treatment regimens forming hormone-resistant prostate cancers are yet to be developed. Among the most important regulators of apoptosis and programmed cell death is the bcl-2 gene and its related proteins. Elevated levels of bcl-2 protein may contribute to the progression of prostate cancers to a metastatic and hormone-insensitive state characterized by poor responses to chemotherapy. OBJECTIVE: To characterize the expression of bcl-2 proteins as a prognostic factor in humans. DESIGN: A retrospective approach. SETTING: Urology section, Federal University of São Paulo. DIAGNOSTIC TEST USED: Immunohistochemical analysis using bcl-2 protein antibody and normal staining by hematoxylin-eosin. MAIN MEASUREMENTS: Prognostic relations and protein expression were evaluated considering the total sample (28) divided into two groups, high (8 to 10) and low (2 to 4), separated according to the histological differentiation grade (Gleason score) with 10 and 18 samples, respectively. RESULTS: The differentiation of grade into two groups separated according to the Gleason score in low and high types presented different bcl-2 expression (P < 0.001). CONCLUSION: The higher frequency of bcl-2 immunostaining in tumor samples was observed in association with more advanced Gleason scores and suggests that an increase in the ratio of this anti-apoptotic protein often occurs during progression of prostate cancers.